The Effect of Tasuka Video on Pre-Reading Interest and Curiosity Character in Group B3 Students of TK Pertiwi DWP Setda Banjarnegara - Nur Subekti (UM Purwokerto Press, 2025)
This study aims to determine the influence of Tasuka's video on pre-reading interest and curiosity character in B3 group students of Pertiwi Kindergarten DWP Banjarnegara Secretariat. The research method used was an experiment with a pre-experimental design with a single control group. The research sample consisted of 30 people who were divided into two groups, namely the experimental group (n=15) and the control group (n=15). The experimental group was given the treatment of watching Tasuka's videos for 15 minutes every day for 2 weeks, while the control group was not given the treatment. Data were collected using observations, field records and documentation. The results showed that there was a significant difference between the experimental group and the control group in terms of pre-reading interest and curiosity character. The experimental group showed increased pre-reading interest and higher curiosity characteristics compared to the control group. This shows that Tasuka's video has a significant influence on pre-reading interest and curiosity character in the B3 group of Pertiwi Kindergarten DWP Banjarnegara Secretariat.